Pendidikan Akhlak Sebagai Ruh Pendidikan Islam - Rahmi Anekasari (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
The development of a globalized world not only produces human productivity in simplifying your life, but it also has adverse effects on human relations and governance patterns. But of progress emerging globalized moral decadence until today. This fact should not only be a commodity social issues just discourse alone, but should be aware of Indonesia that adult education has lost his soul (moral education / educational character), because it is not stable enough to fortify young people (teenagers) from destructive behaviors they consume from a variety of sources of information. Education should be directed to education that is integrated with the values of faith and piety. Education that can see a multidimensional human beings are not only composed of two elements alone (physical and spiritual). The use of Qur'anic method that is able to see humans as being multidimensional, and five strategies that can be used in education morals / these characters is the integration of faith and piety in the vision, mission, goals and strategies of school; optimization of Islamic religious education in schools is not just a